Reservoir Forming Dynamics of Differential Accumulation of Tight Oil in the Yanchang Formation Chang 8 Member in the Longdong Area, Ordos Basin, Central China - Yang, Jingru; Liu, Xianyang; Xu, Wanglin (Frontiers in Earth Science, 2022)
Tight oil is usually accumulated near source rocks after short-distance migration. For the Chang 8 member tight oil reservoir in the Longdong area of the Ordos Basin, however, the tight oil accumulation does not completely follow the source control theory, which states that richer tight oil is found in zones closer to the source rock. The causes behind such differential accumulation need to be investigated. On the basis of previous studies, this paper accurately restores the oil migration dynamics in the main reservoir-forming period by using the latest paleo-hydrodynamic restoration technology through mudstone compaction analysis. The oil migration dynamics are then compared with the start-up pressure gradient of the transport layer along the potential oil migration path during the main reservoir-forming period. Finally, combined with the paleo-structural characteristics during the main reservoir-forming period, the causes for the differential accumulation of tight oil in the Chang 8 member of the Longdong area are analyzed. The results show that: 1) during the main reservoir-forming period, tight oil in the Chang 8 member tended to and could migrate from the north and northeast to the southwest and has accumulated in the nose-like paleo-structure in the southwest; and 2) following the main reservoir-forming period, as the reservoir formation was compacted and the fluid pressure and hydrocarbon generation capacity reduced, oil accumulated nearer the source rock, and to a lesser extent than it did during the reservoir-forming period. In these two stages, changes in the intensity of oil migration dynamics dominated the differential accumulation of tight oil. This study provides a new perspective for similar efforts.